A practical tool to assess regenerative approaches in food businesses - Luiza Amante, Bruna; Mansur Levy, Max Yamauchi; Borrero Camacho, Daniel; Detlefsen Rivera, Guillermo; Vagliente, Pablo (Frontiers, 2025)
Food systems account for approximately 34% of global greenhouse gas emissions. This figure in itself stresses the urgent need for effective solutions that mitigate impacts while ensuring food security. Regenerative Agriculture and Regenerative Food Businesses are emerging as promising approaches to address this challenge. However, it is essential to develop accessible methods to gather and standardize information on regenerative framework to gain stakeholder support and encourage business adoption. This article presents the Initial Perception of the Regenerative Approach (IPRA) tool, designed to provide a rapid and preliminary assessment of the alignment of food businesses in Latin America and the Caribbean (LAC) with the regenerative approach. IPRA evaluates whether a company’s actions, intentions, and narrative are aligned of regenerative principles and practices. Its goal is to generate sufficient data, at low cost, to enable different institutions to analyze and identify business models that align with their interests, prior to investing in more in-depth field studies. The tool comprises four main instruments that support the systematic collection of business information and the evaluation of regenerative attributes across environmental, social, and economic dimensions. A scoring system (0–4) is used, integrated with qualitative data from interviews. The IPRA was employed in the analysis of 55 food businesses drawn from a previous mapping of 181 businesses across the Amazon and Central American Dry Corridor. The results showed that the tool is capable of providing a general overview of the regenerative approach adopted by businesses, as well as enabling comparisons among them. It also serves as a useful resource for stakeholders seeking a deeper understanding of businesses they might be interests in. These findings revealed varying levels of alignment among the businesses, with an overall correspondence with regenerative practices highlighted in existing literature, particularly in agronomic and environmental aspects. The tool proved adaptable, effective, and cost-efficient for gathering data across the food system, including agricultural production, forest food gathering, or commercial processing. This rapid overview offered by the IPRA could play a key role in supporting the urgent development of public policy frameworks and other actions aimed at strengthening and advancing the regenerative approach throughout LAC.